TEACHING FOREIGN LANGUAGES AT THE UNIVERSITY OF ECONOMICS IN BRATISLAVA IN CONNECTION TO THE NEEDS OF THE LABOUR MARKET - Michaela Čiefová; Katarína Seresová (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The objective of the authors of the article was to analyse the labour market from the point of view of languages used by individual foreign companies in Slovakia. Since insufficient language competence of employees is one of the causes of youth unemployment in the European Union, the paper focuses also on language preparation of the students at the University of Economics in Bratislava, and contemplates the fact whether real foreign language knowledge of the graduates meets the requirements of the labour market, and whether the curricula of individual subjects reflect these requirements. English was proven to be the most frequently selected foreign language by the students, followed by German. Since there are many American, British, as well as German and Austrian companies located in Bratislava, we find this situation rather positive. However, we highly recommend students to acquire at least basic knowledge of German in order to increase their competitive advantage.